TANTANGAN PERAWAT DALAM PELAKSANAAN KREDENSIAL UNTUK PENINGKATAN JENJANG KARIR DI RS ISLAM BANJARMASIN - M. Fahrin Azhari; Yustan Azidin, Herman Ariadi, Dewi Setya Paramitha (CV. ADIBA AISHA AMIRA, 2024)
Introduction: Professional nurses according to the book National Accreditation National Standard edition 1.1 are as one of the one Professional Care Provider (PPA). As a PPA who provides care for 24 hours in hospital, it demands that nurses as care professionals must have competence. According to SNARS edition 1.1 hospitals are required to have nursing credential regulations includes evaluation and verification of education, registration, permits, authority, training and experience, Hospitals must also plan for nursing human resources by having qualification standards and Staff Authority (KKS). Purpose: This study aims to explore in depth the challenges of implementation credentials according to the National Hospital Accreditation Standards. Method: The research design used in this research is a qualitative research design with a phenomenological approach . Data were obtained through in-depth interviews with 6 participants and document studies in Islamic Hospital of Banjarmasin. Results: As a result, there are themes of The Challenges of Credentials Implementation with sub-themes of The ideal number between assessors and nurses whose competencies assessed, overlapping task an function of credential team, the incentive salary for Assessors, and The Payment for Nursing Service in accordance with clinical autorithy. Conclusion: Credentials can improve quality, protect patient safety, maintain standards of nursing care services and provide protection to nurses if the implementation of credentials is carried out with the correct process such as adequacy of the number of assessors, salary incentives for assessors, clarity of roles and functions of the credential team and also provision of appropriate salaries/bonus with the burden of action that is the responsibility of the nurse.